PENYULUHAN KONSUMSI DAUN MANGKOKAN (POLYSCIAS SCUTELLARIA) UNTUK MELANCARKAN ASI PADA IBU MENYUSUI - Kasmara, Dwi Pratiwi; Aswan, Yulinda (PITIMAS: Journal of Community Engagement in Health, 2025)
Background: Exclusive breastfeeding coverage in Indonesia remains suboptimal, reaching only 52.5% among infants aged <6 months (Riskesdas, 2021). One of the major contributing factors is hypogalactia or insufficient breast milk production. Traditional use of Polyscias scutellaria (mangkokan leaves) as a herbal galactagogue is common, although scientific evidence remains limited. Objective: This study aimed to determine the effectiveness of health education combined with the consumption of P. scutellaria leaves in improving breastfeeding knowledge among postpartum mothers. Methods: A quasi-experimental pretest–posttest single-group design was applied. Nineteen breastfeeding mothers received structured breastfeeding counseling and consumed mangkokan leaf infusion for 28 days (3 g dried leaves, twice daily). Breastfeeding knowledge was assessed using a standardized questionnaire at pretest (T0) and posttest (T1). Results: The mean knowledge score increased significantly from 60 (pretest) to 95 (posttest), with a mean difference of +35 or a relative increase of 58.3%. This indicates that the intervention effectively improved maternal knowledge. Preclinical evidence supports the lactogenic potential of P. scutellaria, including increased prolactin and oxytocin levels and improved mammary gland histology in animal models. Conclusion: Health education combined with mangkokan leaf consumption significantly enhances breastfeeding knowledge among mothers. Further randomized controlled clinical trials are needed to confirm the efficacy and safety of P. scutellaria in directly increasing breast milk production.